2020
DOI: 10.1152/jn.00339.2020
|View full text |Cite
|
Sign up to set email alerts
|

Early life stress facilitates synapse premature unsilencing to enhance AMPA receptor function in the developing hippocampus

Abstract: Chronic early life stress (ELS) increases vulnerability to psychopathologies and cognitive deficits in adulthood by disrupting the function of related neural circuits. However, whether this disruption emerges early in the developing brain remains largely unexplored. In the current study, using an established limited-bedding and nesting model of ELS in P2-10 mice, we provide direct evidence that ELS caused early modification of hippocampal glutamatergic synapses in the developing brain. We demonstrated that ELS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 48 publications
3
7
0
Order By: Relevance
“…19 Although the experiments in this study are performed in male mice only, accelerated synaptic maturation following ELS exposure is suggested to be independent of sex. 31 Together with our current findings, dynamic and enduring developmental effects of ELS on hippocampal synapses emerge, which are initially characterized by accelerated synaptic maturation of DG granular cells, observed as an increase in mEPSC frequency and amplitude, and altered synaptosomal AMPAR and NMDAR content. With age, enhanced synaptic activity sustains and synaptic GluA3 content increases.…”
Section: ^(I)supporting
confidence: 85%
See 4 more Smart Citations
“…19 Although the experiments in this study are performed in male mice only, accelerated synaptic maturation following ELS exposure is suggested to be independent of sex. 31 Together with our current findings, dynamic and enduring developmental effects of ELS on hippocampal synapses emerge, which are initially characterized by accelerated synaptic maturation of DG granular cells, observed as an increase in mEPSC frequency and amplitude, and altered synaptosomal AMPAR and NMDAR content. With age, enhanced synaptic activity sustains and synaptic GluA3 content increases.…”
Section: ^(I)supporting
confidence: 85%
“…A previous study reported similar effects of ELS on synapses in the hippocampal CA1 area at P11 following the LBN paradigm, demonstrating that ELS prematurely "unsilences" CA1 synapses by enhancing the recruitment of AMPARs at silent synapses. 31 ELS may similarly induce premature synapse unsilencing at DG synapses. Interestingly, we found an overall decrease in synaptic protein levels in synaptosomal fractions of P9 pups that were exposed to ELS with a significant decrease for PSD-95, GluA3 and GluN2B.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations